Nursing interventions in palliative care in primary health care: Scoping review (Research, Society and Development, 2021)
Objective: to map nursing interventions in palliative care in primary health care. Method: This is a scope review. The PRISMA Extension for Scoping Review instrument was used for the writing of the study. Searches were performed in six databases, using the descriptors palliative care, primary health care and nursing care. Results: 23 studies were selected and, from them, 63 nursing interventions were identified, focused on: operationalization of palliative care in primary health care; promotion of qualified and integrated assistance; family/caregiver within the home; pain control; establishing efficient and effective communication; and psychosocial and spiritual changes. Conclusion: The mapping of scientific production showed that, although there have been advances in recent years, nursing interventions in palliative care in primary health care have still been implemented in an incipient way. This fact reflects the need for improved professional training in order to expand access to palliative care and improve the service provided.